Academic Flow: A Systematic Review of the Influencing Factors and Their Impacts on Students - Jayati, Eva Agustina; Kurniawati, Farida (KONSELOR, 2025)
Flow is a source of mental energy because it focuses on attention and motivates the individual to perform an action. The concept of flow was developed by a psychologist named Mihaly Csikszentmihalyi. Csikszentmihalyi studied the flow phenomenon in the 1970s and found that individuals who experience flow will feel total involvement in an activity, which then leads them into an optimal experience. On the other hand, students need academic flow to successfully complete lectures, study, and work assignments. This study aims to determine and to explore factors and impacts of flow for university students. This study used a systematic literature review method based on the PRISMA flow diagram. This study used data from 13 eligible and credible articles. The results demonstrated that students can strive to achieve flow by understanding related factors and impacts. In addition, the abilities are required for educators to foster academic flow. Therefore, although flow is a condition related to students‘ internal conditions, this study shows that flow can also be influenced by external factors.